2020
DOI: 10.18632/aging.103438
|View full text |Cite
|
Sign up to set email alerts
|

circRNA_100859 functions as an oncogene in colon cancer by sponging the miR-217-HIF-1α pathway

Abstract: Circular RNAs (circRNAs) play an important role in cancer development and progression by regulating gene expression. The present study aimed to investigate the function of circRNA_100859 in colon cancer. circRNA expression profiles from a human circRNAs chip were analyzed. The effects of circRNA_100859 on cell proliferation and apoptosis were assessed in vitro and interactions between circRNA_100859 and its micro (mi)RNA and target genes were analyzed. The diagnostic and prognostic signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 25 publications
(2 reference statements)
0
27
0
Order By: Relevance
“…Colon adenocarcinoma is a malignancy that originates from the intestinal epithelium and has a rapid increase in its incidence. Despite remarkable advances in its diagnosis and treatment during the past decades, the prognosis is still not satisfying, with a 5-year survival rate of less than 60% (Zhou et al, 2020). Besides, accumulated evidence supports that frequent postoperative sporadic relapse and/or metastatic recurrence exerts crucial effects on the prognosis of colon adenocarcinoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…Colon adenocarcinoma is a malignancy that originates from the intestinal epithelium and has a rapid increase in its incidence. Despite remarkable advances in its diagnosis and treatment during the past decades, the prognosis is still not satisfying, with a 5-year survival rate of less than 60% (Zhou et al, 2020). Besides, accumulated evidence supports that frequent postoperative sporadic relapse and/or metastatic recurrence exerts crucial effects on the prognosis of colon adenocarcinoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al, 2020 [ 110 ] described circERBIN (hsa_circ_0001492, hsa_circ_000729) in CRC and revealed that circERBIN/miR-125a-5p/miR-138-5p/4EBP-1 axis is leading to activation of the HIF-1α signaling pathway. Hsa_circ_100859 (hsa_circ_0023064) participates in colon cancer progression via sponging of miR-217 and upregulation of the expression levels of HIF-1α (hypoxia-inducible factor-1α) [ 111 ].…”
Section: Oncogenic Functions Of Circrnasmentioning
confidence: 99%
“…These studies mainly described specific human circular RNA and its potential microRNA target. The vast majority of these investigations has been published during the last two years and describes the role of miRNA sponging in breast [ 83 ], lung [ 84 ], colon [ 85 ], and other cancer types [ 86 , 87 ]. Interestingly, some of them, for example, hsa_circ_0009910, potentially play a role in a wide range of malignancies [ 88 ].…”
Section: The Role Of Mirnas In Schizophrenia: Circular Rnas As Spomentioning
confidence: 99%